Motivations and influences in Chinese international doctoral students' decision for STEM study abroad. Issue 3 (27th May 2018) - Yang, Yibo; Volet, Simone; Mansfield, Caroline
Abstract: Despite China's recent remarkable performance in high-quality research, the number of students going abroad to pursue doctoral degrees in STEM fields has been rising rapidly. This study investigates the motivations of Chinese international doctoral students (CIDS) in STEM fields for undertaking a PhD abroad, and the external factors influencing this major life decision. Based on in-depth interviews with 35 CIDS from seven universities in four Australian states, the findings show that for the current generation, enriching life experiences and self-cultivation emerged as most prominent personal motivations. The choice to study abroad, though ultimately a personal decision, was influenced by a range of factors and particularly long-term cooperation between host and home institutions. Both academic and personal reputation of supervisors played important roles in the selection of host institutions. This study may be of value to supervisors and higher education policy-makers, at institutional and government levels in all countries, whether "home" or "host", invested in sustainable international doctoral education.